2002
DOI: 10.1081/erc-120015055
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Available Testosterone Levels Fall Acutely Following Myocardial Infarction in Men: Association With Fibrinolytic Factors

Abstract: The effect of acute myocardial infarction on plasma levels of testosterone in men is unclear. No previous studies have evaluated the bio-available fraction of testosterone. Low plasma testosterone levels have been associated with several risk factors for myocardial infarction, including an unfavorable fibrinolytic profile. In a prospective, case control study, we examined changes in plasma levels of sex hormones, including bio-available testosterone, in patients with acute myocardial infarction and in control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 33 publications
(39 reference statements)
2
28
1
Order By: Relevance
“…The greater the fall in testosterone following MI, the higher PAI-1 activity and lower tPA activity (30), suggesting a similar interaction between testosterone, PAI-1 and tPA. In addition, the anti-thrombotic influence of testosterone maybe potentially lost following an MI (30). Supraphysiological testosterone therapy is also reported to modulate coagulation factor expression.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The greater the fall in testosterone following MI, the higher PAI-1 activity and lower tPA activity (30), suggesting a similar interaction between testosterone, PAI-1 and tPA. In addition, the anti-thrombotic influence of testosterone maybe potentially lost following an MI (30). Supraphysiological testosterone therapy is also reported to modulate coagulation factor expression.…”
Section: Discussionmentioning
confidence: 90%
“…It was reported that testosterone was positively associated with tPA activity and inversely associated with PAI-1 activity and fibrinogen levels (29). Similarly a potentially beneficial effect of testosterone upon coagulation was reported in men in the period after an acute MI (30). Both total and bioavailable testosterone fell transiently in the first 24 h post-infarction.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Testosterone decreased within first 24 hours after myocardial infarction [7]. Helaly et al found that patients with ACS had lower values of fT in comparison to control group [8].…”
Section: Discussionmentioning
confidence: 99%